Rapid regulation of microRNA following induction of long-term potentiation in vivo - Joilin, Greig; Guévremont, Diane; Ryan, Brigid; Claudianos, Charles; Cristino, Alexandre S.; Abraham, Wickliffe C.; Williams, Joanna M. (Frontiers in Molecular Neuroscience, 2014)
Coordinated regulation of gene expression is essential for consolidation of the memory mechanism, long-term potentiation (LTP). Triggering LTP by N-methyl-D-aspartate receptor (NMDAR) activation rapidly activates constitutive and inducible transcription factors that promote expression of genes responsible for LTP maintenance. As microRNA (miRNA) coordinate expression of related genes, we hypothesise that miRNA contribute to the LTP-induced gene response. MiRNA function primarily as negative regulators of gene expression. As LTP promotes a generalised rapid up-regulation of gene expression, we predicted a complementary rapid down-regulation of miRNA. Accordingly, we carried out global miRNA expression profiling in rat dentate gyrus 20 min post-LTP induction in vivo. Consistent with our hypothesis, we found a large number of differentially expressed miRNA, the majority down-regulated. Detailed analysis of miR-34a-5p and miR-132-3p revealed this down-regulation was transient and NMDAR-dependent, whereby block of NMDARs released an activity-associated inhibitory mechanism. Furthermore, down-regulation of mature miR-34a-5p and miR-132-3p occurred solely by post-transcriptional mechanisms, despite up-regulation of the pri-miR-132 transcript. To understand how down-regulation of miR-34a-5p and miR-132-3p intersects with the molecular events occurring following LTP, we used bioinformatics to identify potential targets. Previously validated targets included the key LTP-regulated genes Arc and glutamate receptor subunits. Predicted targets included the LTP-linked kinase, Mapk1, and neuropil-associated transcripts Hn1 and Klhl11, which were validated using luciferase reporter assays. Furthermore, p42-Mapk1 levels were up-regulated following LTP. Together, these data support the interpretation that miRNA, in particular miR-34a-5p and miR-132-3p, make a surprisingly rapid contribution to synaptic plasticity via dis-inhibition of translation of key plasticity-related molecules.